Stabilization of wide band-gap p-type wurtzite MnTe thin films on amorphous substrates. Issue 23 (4th June 2018) - Siol, Sebastian; Han, Yanbing; Mangum, John; Schulz, Philip; Holder, Aaron M.; Klein, Talysa R.; van Hest, Maikel F. A. M.; Gorman, Brian; Zakutayev, Andriy
Abstract : The wurtzite polymorph of MnTe with a wider band gap and moderate p-type doping is stabilized on an amorphous indium zinc oxide substrate. Abstract : An important challenge in the development of optoelectronic devices for energy conversion applications is the search for suitable p-type contact materials. For example, p-type MnTe would be a promising alternative back contact for CdTe solar cells due to their chemical compatibility, but under normal conditions it has a too narrow band gap due to its octahedrally coordinated nickeline (NC) structure. The tetrahedrally coordinated wurtzite (WZ) polymorph of MnTe has not been reported, but it is especially interesting due to its predicted wider band gap and better structural compatibility with CdTe and related II–VI semiconductor materials. Here, we report on the stabilization of WZ-MnTe thin films on amorphous indium zinc oxide (a-IZO) substrates relevant to photovoltaic applications. Optical spectroscopy of the WZ-MnTe films shows a wide direct band gap of E g = 2.7 eV, while photoelectron spectroscopy (PES) measurements reveal weak p-type doping with a Fermi level of 0.6 eV above the valence band maximum. The results of electron microscopy and PES measurements indicate that WZ-MnTe is stabilized due to interdiffusion at the interface with IZO. The results of this work introduce a substrate stabilized WZ-MnTe polymorph as a potential p-type contact material candidate for future applications in CdTe devices for solar energy conversion and other optoelectronic technologies.